2022
DOI: 10.1002/path.5978
|View full text |Cite
|
Sign up to set email alerts
|

Peak density of immature nerve cells occurs with high‐grade dysplasia in intraductal papillary mucinous neoplasms of the pancreas

Abstract: The development of neural structures within tumors is now considered vital for carcinogenesis. However, the time course of this development in human pre‐invasive neoplasia has been incompletely described. Therefore, we performed a detailed analysis of nerves across the neoplastic spectrum in resected intraductal papillary mucinous neoplasms (IPMNs) of the pancreas. Histology and multiplexed immunochemistry demonstrated that nerve density increased from low‐grade (LG) to high‐grade dysplasia (HG) but did not fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Intriguingly, our H&E staining results showed that nerve density in the stroma surrounding the tumor markedly increased (Fig. 11 a–d), which probably indicates the degree of malignancy [ 17 ]. IHC staining indicated that FOXP3 + Tregs mostly accumulated in the invasive fronts of OSCC tissues but were sporadically distributed throughout the tumor.…”
Section: Resultsmentioning
confidence: 96%
“…Intriguingly, our H&E staining results showed that nerve density in the stroma surrounding the tumor markedly increased (Fig. 11 a–d), which probably indicates the degree of malignancy [ 17 ]. IHC staining indicated that FOXP3 + Tregs mostly accumulated in the invasive fronts of OSCC tissues but were sporadically distributed throughout the tumor.…”
Section: Resultsmentioning
confidence: 96%
“…The gut microbiome may play a role in pancreatic cancer initiation and progression, and thus, the role of the pancreatic microbiota in the cystic liquid can be assessed for the detection of IPMN malignancy [ 89 ]. In tissue sample biopsy, the growth of neural structures within tumors is now considered a vital factor for carcinogenesis [ 90 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…In tissue sample biopsy, the growth of neural structures within tumors is now considered a vital factor for carcinogenesis [90].…”
Section:  Diagnosismentioning
confidence: 99%